Re6Q8(SO3)610- (Q = S or Se): Facile Synthesis and Properties of the Most Highly Charged Octahedral Cluster Complexes and High Magnetic Relaxivity of Their Colloids with Gd3+ Ions - Brylev, Konstantin A; Akhmadeev, Bulat S; Elistratova, Julia G; Nizameev, Irek R; Gubaidullin, Aidar T; Kholin, Kirill V; Kashnik, Ilya V; Kitamura, Noboru; Kim, Sung-Jin; Mironov, Yuri V; Mustafina, Asiya R (Inorganic chemistry, 2019)
New octahedral rhenium cluster complexes [Re6Q8(SO3)6]10- (Q = S or Se) were synthesized starting from [Re6Q8(H2O)4(OH)2]·12H2O. The complexes were crystallized as sodium salts and characterized by X-ray single-crystal diffraction and elemental analyses, IR, UV/vis and luminescence spectroscopies. Magnetic relaxation data demonstrate the complex formation of the cluster units with gadolinium ions. The analysis of the magnetic relaxation rates measured at various Gd:cluster ratios and different concentrations revealed the conversion of the aggregates (Gdx[Re6Se8(SO3)6]y)n- into a nanoparticulate form even at x = 1 and y ≥ 1. Thus, the self-assembly of the cluster units into the nanoparticles is greatly facilitated by counterion binding with sodium cations. The concentration conditions were optimized for the formation and hydrophilization of NaxGdy[Re6Q8(SO3)6]-based colloids with the magnetic relaxivity values of r1(2) = 21.0(24.1) and r1(2) = 25.9(29.8) mM-1 s-1 for the {Re6S8}2+ and {Re6Se8}2+ derivatives, respectively.New octahedral rhenium cluster complexes [Re6Q8(SO3)6]10- (Q = S or Se) were synthesized starting from [Re6Q8(H2O)4(OH)2]·12H2O. The complexes were crystallized as sodium salts and characterized by X-ray single-crystal diffraction and elemental analyses, IR, UV/vis and luminescence spectroscopies. Magnetic relaxation data demonstrate the complex formation of the cluster units with gadolinium ions. The analysis of the magnetic relaxation rates measured at various Gd:cluster ratios and different concentrations revealed the conversion of the aggregates (Gdx[Re6Se8(SO3)6]y)n- into a nanoparticulate form even at x = 1 and y ≥ 1. Thus, the self-assembly of the cluster units into the nanoparticles is greatly facilitated by counterion binding with sodium cations. The concentration conditions were optimized for the formation and hydrophilization of NaxGdy[Re6Q8(SO3)6]-based colloids with the magnetic relaxivity values of r1(2) = 21.0(24.1) and r1(2) = 25.9(29.8) mM-1 s-1 for the {Re6S8}2+ and {Re6Se8}2+ derivatives, respectively.